Alpenblick : Die zeitgenössische Kunst und das Alpine. - Aigner, Carl; Appelt, Siegrun; Curiger, Bice; Doswald, Christoph; Gander, Mario; Ghirri, Luigi; Hochhauser, Bettina; Huber, Stephan; Kos, Wolfgang; Krois, Erich; Long, Richard; Matt, Gerald; et al. (Wien : Kunsthalle Wien, 1997)
Appelt, Siegrun ; Attersee, Christian Ludwig ; Banz, Stefan ; Brandl, Herbert ; Breitwieser, Irma ; Buri, Samuel ; Byars, James Lee ; Cahn, Miriam ; Disler, Martin ; Doig, Peter ; Eiter, Martin ; Faganello, Flavio ; Faure, Nicolas ; Fila, Rudolf ; Fischli & Weiss ; Franz, Hannes ; Fulton, Hamish ; Gander, Mario ; Gette, Paul-Armand ; Ghirri, Luigi ; Gursky, Andreas ; Hell, Bodo ; Hodel/Schumacher/Clavadetscher ; Huber, Stephan ; Hunstein, Stefan ; Hütte, Axel ; Huttenlocher, Britta ; IRWIN ; Klinkan, Alfred ; Kneffel, Karin ; Kolig, Cornelius ; Kelley, Mike ; McCarthy, Paul ; Lang, Nikolaus ; Lassnig, Maria ; Gac, Jean Le ; Leitner, Paul Albert ; Long, Richard ; Marclay, Christian ; Mosbacher, Alois ; Rosenblum, Adi ; Muntean, Markus ; Niederer, Caro ; Niedermayr, Walter ; Painitz, Hermann J. ; Peintner, Max ; Penone, Giuseppe ; Pilhofer, Josef ; Pongratz, Peter ; Raetz, Markus ; Rainer, Arnulf ; Rappenecker, Gert ; Richter, Gerhard ; Roth, Dieter ; Salner, Georg ; Salvo ; Sandoz, Claude ; Schlegel, Eva ; Schnyder, Jean-Frederic ; Brunner, Norbert ; Schuster, Michael ; Signer, Roman ; Smith, Bridget ; Spiluttini, Margherita ; Stimm, Thomas ; Strobl, Ingeborg ; Trenkwalder, Elmar ; Vigouroux, Christophe ; Weigand, Hans ; Weiler, Max ; Weinberger, Lois ; Weissman, Benjamin ; Winteler, Anna ; Zechyr, Othmar
biografie
Alpenblick : Die zeitgenössische Kunst und das Alpine, Kunsthalle Wien, 31. Oktober 1997 bis 1. Februar 1998
Duits
kunstcatalogus
Keywords: Alpen